Presupposition and Assertion of The Main Character in The School for Good and Evil Novel - Luh Pramitha Maheswari; I Made Sena Darmasetiyawan; Yana Qomariana (LPPM Universitas Dhyana Pura, 2025)
In writing a literary work, every sentence created by a writer has a purpose of conveying information to the readers, which can be understood by analyzing the presupposition and assertion within each sentence. In this sense, the present study aims on examining how information is organized in the fantasy novel The School for Good and Evil, specifically portraying through the main character. The data for this study was taken from the main character’s utterances within dialogues in the novel, limited to the sentence-level forms. To collect the data from the novel, a documentation method with stratified sampling technique was applied. In this case, the story was divided into five different plot stages with five utterances were selected for each strata, resulting in a total of 25 data for the analysis. Additionally, the present study also applied a qualitative method following the theory of information structure by Lambrecht (1994). These elements were examined to understand how information is structured and what is assumed to be known or introduced as new to the readers. In the result, it revealed that the writer intentionally organize sentences to share information regarding the story in the main character’s utterances throughout the narrative.